Clinical performance in ERN eUROGEN for penile, testicular, adrenal and soft tissue cancers. Issue 3 (March 2022) - Ashley, Sophie; Shilhan, Darren; Battye, Michelle; Meyer, Christian; Mancini, Mariangela; Ayres, Benjamin; Muneer, Asif; Albersen, Maarten; Feitz, Wout; Langenhuijsen, Johan Ferdinand; Sangar, Vijay
Abstract: Background: European Reference Network (ERN) eUROGEN is a cross-border collaboration set up by the European Commission in 2017 aimed at tackling rare urogenital conditions, including cancers. Objective: This report aims to assess ERN eUROGEN's operational activity with a focus on rare urogenital cancers. Design, Setting and Participants: Data for descriptive analyses were collected retrospectively between 2013 and 2017, and prospectively between 2018 and 2020. Outcome measurements and statistical analysis: Operational indicators were set by the European Commission from 2018. Additionally, in 2019/20 centres self-assessed clinical service provision and provided clinical metrics for rare cancer specialist centres as established by experts. Results and Limitations: Results revealed that the cumulative rare urogenital cancer population increased 519.8% from 1, 631 in 2013 to 10, 109 in 2020. This may provide opportunities for research and creation of a large cancer registry. In total, ten centres met the clinical requirements for rare cancer specialist centres providing evidence of high-volume. Differences in data collection methods between centres limit further analyses. Other rare cancer data identified 39 panel discussions, three webinars, and eight publications. Conclusions: Whilst limitations to data analysis remain, ERN eUROGEN has demonstrated excellent operational performance with promising opportunities for rare cancer research. Highlights: Analysis on ERN eUROGEN activity with a focus on rare urogenital cancers. The number of patients and procedures at rare cancer specialist centres increased. A large specific data registry for 25 years is currently being constructed. ERN eUROGEN has contributed to rare urogenital cancer education and research. Future possibilities for rare cancer research are discussed.